(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
As a result of the reforms carried out in our country in recent years, a number of important works have been carried out in the fight against drug and human trafficking, and new work methods are being implemented in the early prevention of crimes and the fight against violations.